1990
DOI: 10.1139/y90-050
|View full text |Cite
|
Sign up to set email alerts
|

Corelease of neuropeptide Y like immunoreactivity with catecholamines from the adrenal gland during splanchnic nerve stimulation in anesthetized dogs

Abstract: The release of neuropeptide Y like immunoreactivity (NPY-li) from the adrenal gland was studied in relation to the secretion of catecholamines (CA: NE, norepinephrine; E, epinephrine) during the left splanchnic nerve stimulation in thiopental-chloralose anesthetized dogs (n = 16). Plasma concentrations of NE, E, and NPY-li were determined in the left adrenal venous and aortic blood. Adrenal outputs of NPY-li, NE, and E were 2.4 +/- 0.4, 1.4 +/- 0.2, and 7.3 +/- 1.7 ng/min, under basal conditions, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 8 publications
2
2
0
Order By: Relevance
“…It has been reported that NPY release correlates with catecholamines in the cat (Lundberg et al, 1986). Similar results were seen in the dog: a 40-Hz burst of electrical stimulation caused a 2-fold increase in the release of NPY, which was significantly correlated with both adrenaline and noradrenaline release (Briand et al, 1990). The effect appears to be mediated by acetylcholine acting through the nicotinic receptor, as the nicotinic receptor antagonist, hexamethonium, was found to abolish the effect of splanchnic nerve stimulation (Allen et al, 1984) and in retrograde perfusion experiments stimulation of the nicotinic receptor caused the release of NPY, an effect which was antagonised by hexamethonium (Hexum et al, 1987).…”
Section: Role Of the Splanchnic Nerve In Regulatingsupporting
confidence: 82%
“…It has been reported that NPY release correlates with catecholamines in the cat (Lundberg et al, 1986). Similar results were seen in the dog: a 40-Hz burst of electrical stimulation caused a 2-fold increase in the release of NPY, which was significantly correlated with both adrenaline and noradrenaline release (Briand et al, 1990). The effect appears to be mediated by acetylcholine acting through the nicotinic receptor, as the nicotinic receptor antagonist, hexamethonium, was found to abolish the effect of splanchnic nerve stimulation (Allen et al, 1984) and in retrograde perfusion experiments stimulation of the nicotinic receptor caused the release of NPY, an effect which was antagonised by hexamethonium (Hexum et al, 1987).…”
Section: Role Of the Splanchnic Nerve In Regulatingsupporting
confidence: 82%
“…In support of this hypothesis, Bereiter [24] found adrenal blood flow to be correlated with MAP after partial cervical spinal cord transection in cats, and Jasper et al [ 17] reported that blood flow to the adrenal capsule, cortex and medulla was correlated with MAP after hypo tensive hemorrhage in anesthetized dogs. Other studies, however, found no relationship between total adrenal blood flow and changes in MAP produced by insulin [25], endotoxin shock [26], carotid artery occlusion [27], hypo xia [28], splanchnic stimulation [27,29,30], or both normotensive and hypotensive hemorrhage [31]. Considered as a whole, our data support a correlation between changes in MAP and adrenal blood flow.…”
Section: Adrenal Blood Flow and Ca Secretionsupporting
confidence: 59%
“…The release of adrenal CRF is stimulated by haemorrhage in dogs (81), and by splanchnic nerve stimulation in calves the rat does not appear to be regulated by splanchnic nerve activity (24) and stimulation of the peripheral end of the splanchnic nerve has no significant effect on release of NPY from the adrenals in conscious calves (32). In cats and dogs, however, NPY release is increased by splanchnic nerve stimulation, and the release of NPY is significantly correlated with catecholamine release (46). The adrenal content of NPY is influenced by age, nutritional status (47), and 'stress' as insulin-induced hypoglycaemia causes rapid turnover of adrenal NPY (48).…”
Section: The Innervation Of the Adrenal Cortexmentioning
confidence: 99%